2011
DOI: 10.1007/s11547-011-0619-9
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for complications of CT-guided lung biopsies

Abstract: The size of the lesion and the length of the intrapulmonary trajectory are risk factors for pneumothorax and parenchymal haemorrhage. The transfissural course of the needles is frequently related to pneumothorax and intrapulmonary haemorrhage, and the type of the needle is related to pneumothorax.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 31 publications
3
27
0
Order By: Relevance
“…In this study, pneumothorax occurred in 29% of cases, within the range of 8%-64% reported in the literature (1)(2)(3)(4)(5)(6)(7)(17)(18)(19)(20). Pulmonary hemorrhage was relatively frequent in our experience (27%) compared to the incidence reported in the literature (15%-26%) (8).…”
Section: Discussionsupporting
confidence: 65%
“…In this study, pneumothorax occurred in 29% of cases, within the range of 8%-64% reported in the literature (1)(2)(3)(4)(5)(6)(7)(17)(18)(19)(20). Pulmonary hemorrhage was relatively frequent in our experience (27%) compared to the incidence reported in the literature (15%-26%) (8).…”
Section: Discussionsupporting
confidence: 65%
“…We have associated lesion size and malignant histological diagnosis with an increased risk of hemorrhage. Small lesion size and the extent of intrapulmonary needle trajectory are already considered risk factors for both pneumothorax and hemorrhage (30). Previous studies supported this association only as concerns pneumothorax, whereas bleeding risk was associated with CT signs of emphysema (31).…”
Section: Discussionmentioning
confidence: 95%
“…The New York Early Lung Cancer Action Project (ELCAP) group [11] reported good diagnostic performance for CT-guided biopsy (overall 82% sensitivity and 88% accuracy), although the results were less good for nodules <8 mm. However, CT-guided biopsy is highly operator dependent and sensitivity can be very low [28].…”
Section: Discussionmentioning
confidence: 99%